Abe Lincoln at last! - Osborne, Mary Pope.; Murdocca, Sal (New York : Random House, 2011)
The magic tree house whisks Jack and Annie to Washington D.C. in the 1860s where they meet Abraham Lincoln and collect a feather that will help break a magic spell.
"A Merlin Mission."
Keywords: Lincoln, Abraham, -- 1809-1865 -- Juvenile fiction; White House (Washington, D.C.) -- Juvenile fiction; Time travel -- Juvenile fiction; Magic -- Juvenile fiction; Brothers and sisters -- Juvenile fiction; Presidents -- Family -- Juvenile fiction; Fantasy fiction